Pojęcie „poezji religijnej” w kontekście zjawiska sekularyzacji (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
The subject of this article is the concept of “religious poetry” formulated by Jasińska-Wojtkowska. It attempts to answer the question of what correction to this definition is made by taking into account the context of the secularisation of culture, with particular reference to Taylor’s “secular age”. If we accept, that salvaging the presence of religion in the secular age means minimising its confessionality and responding to transcendence through a search for wholeness, then the emphasis in the definition needs to be shifted – the relationship between religiosity and the confessional context of literature should be loosened. A poetic work, representative of the sensibility of the “secular age”, is one that minimises the confessional aspect of spiritual experience and maximises the individual search for wholeness present in it.